Bottlenose dolphin (Tursiops truncatus) vocalizations in response to a stimulus: Behavioral contex and demographic variability - Lopes, Melissa M. (Scholarly Repository, 2012)
Marine mammal survival and fitness depends heavily upon a highly developed sense of hearing. Odontocetes, or toothed whales, rely primarily on sound for communication, navigation, and foraging. As a representative and ubiquitous species of this suborder, both wild and captive populations of bottlenose dolphins (Tursiops truncatus) have been extensively studied. Studies conducted at managed care facilities have contributed to the identification and characterization of their diverse vocal repertoires. Dolphins are known to use single and patterned clicks and whistles to communicate different types of information. However, the behavioral context associated with these vocalizations is currently understudied and limited to broad behavioral categories (e.g., traveling, foraging, and resting). The purpose of this study is to investigate the vocalizations of bottlenose dolphins in managed care in response to a novel stimulus, including an assessment of behavioral correlates and demographic variation in response. I conducted this study at Dolphins Plus, a marine mammal managed care facility in Key Largo, FL, over the course of three months (August-October, 2012). The primary objective of this study was to identify the types of behaviors exhibited by dolphins in association with vocalizations emitted in response to a novel object. The novel object used in this study was a unique apparatus consisting of a large reflective surface, a hydrophone and four video cameras. I utilized the testing apparatus as a stimulus to elicit a reaction (behavioral and vocal) from the animals, which was recorded and analyzed. In addition, I analyzed the effect of various demographic variables, including age and sex, on animal response. Data were collected during 20-minute trials in which the apparatus was placed into the enclosure within the same time frame and location each day and then removed. Recordings and observations from each trial were analyzed to determine if there were any significant relationships between specific types of behaviors and vocalizations among individual dolphins, in addition to assessing the influence of age and sex on response. This study provides evidence of differing effects of a stimulus on behavioral and vocal responses, over time and across demographics. Of all behaviors analyzed (aggression, orientation, sociality) orientation was exhibited with the greatest frequency and social interactions were more frequent than solo interactions. Of all vocalizations analyzed (whistles, echolocation clicks, burst-pulsed yells), clicks were exhibited with the greatest frequency and yells with the least. Adults and females exhibited the most aggressive responses and calves exhibited the most social interactions of all age classes. Clicks were found to be positively correlated with orientation and yells were positively correlated with aggression and orientation. Between novel and non-novel trials, aggression was exhibited with greater frequency during non-novel trials. The apparatus utilized in this study may have been perceived as an aversive stimulus to individuals, and sensitization may have resulted in the observed differences in behavioral and vocal responses over time.